استخدام طرائق النمذجة الرياضية لحل مشاكل غير خطية - سلمان, سعد محسن (Al-Nahrain Journal of Science, 2018)
In this paper, we will study the method of model building which is a fundamental approach in the theory of operation research for solving non-linear real life problems. The solutions are obtained using Lagrange multipliers method, and the results are explained using real life problem.